Adhesion and debonding kinetics of photovoltaic encapsulation in moist environments. (27th July 2015) - Novoa, Fernando D.; Miller, David C.; Dauskardt, Reinhold H.
Abstract: Debonding of photovoltaic (PV) encapsulation in moist environments is frequently reported but presently not well understood or quantified. Temperature cycling, moisture, and mechanical loads often cause loss of encapsulation adhesion and interfacial debonding, initially facilitating back‐reflectance and reduced electrical current, but ultimately leading to internal corrosion and loss of module functionality. To investigate the effects of temperature ( T ) and relative humidity (RH) on the kinetics of encapsulation debonding, we developed a mechanics‐based technique to measure encapsulation debond energy and debond growth rates in a chamber of controlled environment. The debond energy decreased from 2.15 to 1.75 kJ m −2 in poly(ethylene‐co‐vinyl acetate) (EVA) and from 0.67 to 0.52 kJ m −2 in polyvinyl butyral when T increased from 25 to 50°C and 20 to 40°C, respectively. The debond growth rates of EVA increased up to 1000‐fold with small increases of T (10°C) and RH (15%). To elucidate the mechanisms of environmental debonding, we developed a fracture‐kinetics model, where the viscoelastic relaxation processes at the debonding‐tip are used to predict debond growth. The model and techniques constitute the fundamental basis for developing accelerated aging tests and long‐term reliability predictions for PV encapsulation. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We developed a mechanics‐based technique to measure the encapsulation debond energy in EVA (0.67 to 0.52 kJ m −2 ), polyvinyl butyral (0.67 to 0.52 kJ m −2 ), and other elastomeric PV encapsulations. We used a load‐relaxation method to characterize the debond growth rates of EVA that increased up to 1000‐fold with small increases of T (10°C) and RH (15%). We developed a fracture‐kinetics model to elucidate the mechanisms of environmental debonding that can be used to develop accelerated aging tests and long‐term reliability predictions.